2007
DOI: 10.4171/jems/95
|View full text |Cite
|
Sign up to set email alerts
|

Maximizers for the Strichartz Inequality

Abstract: Abstract. We compute explicitly the best constants and, by solving some functional equations, we find all maximizers for homogeneous Strichartz estimates for the Schrödinger equation and for the wave equation in the cases when the Lebesgue exponent is an even integer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
248
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(258 citation statements)
references
References 7 publications
9
248
0
1
Order By: Relevance
“…To verify it, it seems natural to first compute S N −1 and then to use a perturbation argument to establish (1.2). In fact, by a remarkable work of Foschi [14] (see also [21,5]), the value of S N −1 is known for N = 2 and N = 3. We cite the following conjecture from [14]; see also [21].…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…To verify it, it seems natural to first compute S N −1 and then to use a perturbation argument to establish (1.2). In fact, by a remarkable work of Foschi [14] (see also [21,5]), the value of S N −1 is known for N = 2 and N = 3. We cite the following conjecture from [14]; see also [21].…”
Section: )mentioning
confidence: 99%
“…In fact, by a remarkable work of Foschi [14] (see also [21,5]), the value of S N −1 is known for N = 2 and N = 3. We cite the following conjecture from [14]; see also [21].Assuming that this conjecture is true we can generalize an argument from [12,29] and obtain existence of a maximizer for the R d+1 problem. In connection with Conjecture 1.2 we would like to mention that the existence and precompactness problem for the optimization corresponding to S d was solved by Kunze [23] in d = 1 and by Shao [28] in d ≥ 1.…”
mentioning
confidence: 99%
“…For the problem of existence of such optimal S ‫ރ‬ schr and explicitly characterizing the maximizers, Kunze [2003] treated the d = 1 case and showed that maximizers exist by an elaborate concentration-compactness method. Foschi [2007] explicitly determined the best constants when d = 1, 2, and showed that the only maximizers are Gaussians up to the natural symmetries associated to the Strichartz inequality by using the sharp Cauchy-Schwarz inequality and the space-time Fourier transform. Hundertmark and Zharnitsky [2006] independently obtained this result by an interesting representation formula of the Strichartz inequalities in lower dimensions.…”
Section: The Linear Profile Decomposition For the Airy Equation 87mentioning
confidence: 99%
“…x Re(e i(·)a n φ) L ‫ޒ‬ airy , the explicit φ had been uniquely determined by Foschi [2007] and Hundertmark and Zharnitsky [2006] independently: they are Gaussians up to the natural symmetries enjoyed by the Strichartz inequality for the Schrödinger equation.…”
Section: The Linear Profile Decomposition For the Airy Equation 87mentioning
confidence: 99%
“…Sharp constants and maximisers have been calculated for a number of space-time estimates for dispersive equations (see for example [1,9,13,15,22,27]). Proving the existence of such maximisers has also received attention (see for example [4,7,8,10,11,19,24,26]).…”
Section: Introductionmentioning
confidence: 99%